FEATURES OF THE COURSE OF DIABETIC NEUROSTEOARTHROPATHY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Djuraeva Zilola Aramovna; Asliddinova Sevara; Qodirova Feruza; Valijonova To`maris (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Diabetic neuroosteoarthropathy (DNOA, Charcot foot) is a relatively rare complication of diabetes mellitus (DM), which can lead not only to impaired support function of the lower limb in such patients, but also to high amputation. DNOAP is characterized by persistent aseptic inflammation of the bone structures of the foot, which creates significant difficulties in planning treatment measures[1,2,3,4]. In the medical literature, there is data demonstrating the role of individual cytokines and neurohumoral factors in the prolongation of the inflammatory process in diabetes, however, studies identifying significant markers Aseptic inflammation with DNOAP is currently extremely rare[5,6,7].